2015
DOI: 10.1161/hypertensionaha.114.04023
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Relation to Environmental Lead Exposure in the National Health and Nutrition Examination Survey 2003 to 2010

Abstract: Abstract-In view of the declining environmental lead exposure in the United States, we analyzed the National Health and Nutrition Examination Survey (2003-2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 20 publications
3
46
2
Order By: Relevance
“…Hara showed that the low levels of lead that exist today in the USA have little influence on blood pressure 30. As a national randomly sampled, non-institutionalised civilian study, it is significant that the association between log BLL and blood pressures was investigated in non-smoking healthy Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…Hara showed that the low levels of lead that exist today in the USA have little influence on blood pressure 30. As a national randomly sampled, non-institutionalised civilian study, it is significant that the association between log BLL and blood pressures was investigated in non-smoking healthy Koreans.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the epidemiological studies available from 1980 to 2001 reported that a 2-fold increase in blood lead concentration was associated with a 1.0 mm Hg increase in systolic blood pressure and a 0.6 mm Hg increase in diastolic blood pressure [11]. Recent data have suggested that the effect sizes in the associations of blood pressure and blood lead (mean of 1.51 μg/dL) are small and inconsistent [6], or that a modest association was found [12]. …”
Section: Introductionmentioning
confidence: 99%
“…12 Most of these studies contrasted blacks from African ancestry with whites in the United States. However, we recently reported that the prevalence of hypertension on conventional BP measurement, amounted to 13.3% and 28.9%, respectively, among South Africans and Flemish whites and to 34.1% among black South Africans.…”
mentioning
confidence: 99%